Gastrin levels in serum and bronchoalveolar lavage fluid of patients with lung cancer: comparison with patients with chronic obstructive pulmonary disease. Issue 12 (December 1996) - Dowlati, A.; Bury, T.; Corhay, J. L.; Weber, T.; Lamproye, A.; Mendes, P.; Radermecker, M.
Abstract : BACKGROUND: The gastrin gene is known to be expressed in all classes of bronchogenic carcinomas. Furthermore, high levels of gastrin have been reported in both the bronchoalveolar lavage (BAL) fluid and serum of patients with lung cancer. Based on these preliminary data a study was conducted to evaluate the usefulness of gastrin measurements in the diagnosis and staging of lung cancer. METHODS: Thirty-five patients with lung cancer (26 non-small cell (NSCLC) and nine small cell (SCLC)) and 25 patients with chronic obstructive pulmonary disease underwent fibreoptic bronchoscopy and BAL. Gastrin levels were determined in both BAL fluid and the serum and compared with each other and with staging. RESULTS: No difference was found between the gastrin levels in the BAL fluid or serum of the study groups. There was no correlation with the stage in NSCLC and no correlation was found between the gastrin levels in the serum and the BAL fluid. A significant difference was seen in gastrin levels in BAL fluid between extensive and limited SCLC (p < 0.05). CONCLUSION: There is no evidence of clinical usefulness for gastrin measurements in lung cancer.